1971
DOI: 10.1111/j.1475-682x.1971.tb01201.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Suicide Rates among Occupational Categories

Abstract: The correlation between the NORC prestige scale of 1947 with 1950 suicide rates is extremely low for thirty‐six specific occupations. The low correlation calls into question the findings of previous studies which employed gross occupational categories and impressionistic prestige rankings. The results indicate that client dependency and two multivariate models, status inconsistency and distributive justice, deserve further exploration in predicting suicide rates for occupations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

1982
1982
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
1
21
1
Order By: Relevance
“…A frequently cited study from the United States showed that the suicide rate of police officers was 47.6 per 100,000 per year in 1950 (Guralnick, 1963; Labovitz & Hagedorn, 1971). This was the second highest suicide rate among 36 occupations (Labovitz & Hagedorn, 1971). Stack & Kelley (1994) analyzed data from 16 states in 1985 ( N = 33), a sample representing all regions of the nation.…”
Section: Resultsmentioning
confidence: 99%
“…A frequently cited study from the United States showed that the suicide rate of police officers was 47.6 per 100,000 per year in 1950 (Guralnick, 1963; Labovitz & Hagedorn, 1971). This was the second highest suicide rate among 36 occupations (Labovitz & Hagedorn, 1971). Stack & Kelley (1994) analyzed data from 16 states in 1985 ( N = 33), a sample representing all regions of the nation.…”
Section: Resultsmentioning
confidence: 99%
“…Occupations such as sole business operator and physician would be expected to have more suicide risk than machinists and mail carriers, who are not directly dependent on clients for the source of their livelihood. In a pilot study of 36 occupations, Labovitz and Hagedorn (1971) found a mean suicide rate of 40.5 per 100,000 for persons in client-dependent occupations versus a mean of 25.9 per 100,000 for persons in non-client-dependent occupations. Gibbs and Martin's (1964) theory of status integration provides a framework for predicting occupational stress.…”
Section: Internal Occupational Stressmentioning
confidence: 98%
“…Lalli and Turner (1968) provide national data from 1950 but for only six general occupational categories for males ages 20-64. Labovitz and Hagedorn (1971) present data on suicide rates for 36 selected specific occupations for males in 1950. Many specific occupations are found in only one of the articles.…”
Section: Previous Work On Occupation and Suicidementioning
confidence: 99%
See 1 more Smart Citation
“…Various occupational stressors, including dependence on clients for livelihood (Labowitz and Hagedorn 1971), social isolation (Stack 1996), a demanding job with low autonomy (Karasek 1979), high effort with low reward (Siegrist and others 1990) and long working hours are pertinent, but not unique, to the veterinary profession. No specific occupational factors have been linked to suicidal behaviour in veterinarians (Platt and others 2012).…”
Section: Introductionmentioning
confidence: 99%